An investigation into the sources of depreciations in Mongolian Tugrik exchange rate: A structural VAR approach - Gunbileg Ganbayar (Journal of Risk and Financial Management, 2021)
This paper empirically investigates the sources of fluctuations in real and nominal Mongolian Tugrik (MNT) exchange rates by estimating the structural vector autoregressive (SVAR) model over the period January 1994-May 2021 and decomposing the exchange rate series into stochastic components induced by real and nominal shocks under the assumption of the long-run neutrality of nominal shocks on the real exchange rate level. The empirical results show that the real MNT exchange rate movements are primarily due to the real shocks, while the nominal shocks have a major role in explaining nominal exchange rate movements in the short and long run. The nominal exchange rate shows a delayed over-shooting occurring between one and three years after a nominal shock hits the economy. The long-run effect of a monthly one standard deviation nominal shock on nominal MNT exchange rate is 2.5%, which results in a permanent divergence between real and nominal MNT exchange rate and causes non-cointegrated relation between real and nominal MNT exchange rates. The historical decomposition of forecast error indicates that the nominal shock plays a significant role in explaining the depreciation in nominal MNT exchange rate over the last three decades. Our recommendation is to stop 'cash handling' policy, minimize monetary shock, and coordinate fiscal and monetary policies to avoid large nominal depreciation.
Keywords: C32; F31; 330; SVAR; long-run restriction; real shock; nominal shock; Mongolian Tugrik